The Sipakatau dalam Masyarakat Bugis Bone Perspektif Al-Quran - SUBHAN BAKRI (MAGHZA, 2020)
As the times and advances in human civilization, the noble values ​​of culture began to be forgotten by the current generation. Sipakatau culture has become one of the cultures that is almost forgotten by Bugis humans. The term sipakatau which means "humanizing each other", seems to be a daily verbal expression that is often heard, but far from comprehension and practice. The challenge for every nation in the world is how the noble values ​​that have taken root in the cultural lives of the ancients can be maintained and actualized by keeping abreast of increasingly rapid times. Sipakatau culture is not something new in Islam. Sipakatau is a noble character that can also be found in the verses of the Qur'an. This type of research is field research that uses two kinds of data sources, namely primary and secondary sources. Data collection methods used were observation, interviews, and documentation using interpretive, phenomenological, and sociological approaches. The embodiment of civil servants is distinguished from civil servants in the family and civil servants. The whole form is in the form of manner and speech with courtesy as a form of appreciation to man himself and to Allah as the creator of man.